Kajian Pustaka: Analisis Faktor Predisposing, Reinforcing, dan Enabling dengan Partisipasi Masyarakat Mengenai Mitigasi Bencana Banjir - Risyad Aldian Daniel; Novrikasari Novrikasari; Mohammad Zulkarnain (Jurnal Pengabdian Ilmu Kesehatan, 2025)
This study was motivated by the complexity of flooding issues, which require synergy between knowledge, attitudes, social support, and the availability of resources to create effective community participation. The purpose of this study was to analyze how the three main factors in the PRECEDE model predisposing, reinforcing, and enabling affect the level of community involvement in flood mitigation. A qualitative approach using a literature study method was used to gain an in-depth understanding of the determinants of community behavior based on empirical and conceptual studies from various scientific sources. Data was obtained through a search of journals, research reports, and public policies relevant to the context of hydrometeorological disaster mitigation. The results of the study show that predisposing factors such as knowledge and attitudes have a dominant influence on community preparedness, while reinforcing factors such as social support and community leaders strengthen the sustainability of participation. Enabling factors, which include infrastructure, policies, and access to information, have been proven to increase the community's ability to take preventive action. These findings confirm that the effectiveness of flood mitigation depends on the synergistic integration of these three factors to create a community that is adaptive, resilient, and empowered in facing the threat of disasters in a sustainable manner.